(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2010)
Keywords: coronary artery disease; post CABG sociodemography; clinico-pathology; myocardial infarction DOI: 10.3329/jcmcta.v20i2.5619 Journal of Chittagong Medical College Teachers’ Association 2009: 20(2):12-15